Erratum: Impact of the coronavirus disease 2019 (COVID-19) pandemic on the care of patients with acute and chronic aortic conditions (European Journal of Cardio-Thoracic Surgery (2021) 59 (1096-1102) DOI: 10.1093/ejcts/ezaa452) - Czerny, M (Oxford University Press (OUP), 2022)
10.1093/ejcts/ezab314